2016
DOI: 10.1177/0016986216630600
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Relationship Between Three Common Psychopathologies—ADHD, Anxiety, and Depression—and Indicators of Little-c Creativity

Abstract: There is a long-standing controversy over the relationship between psychopathology and creativity. Yet there is a lack of evidence regarding the relationship between common psychopathologies and indicators of little-c, or every day, creativity among laypeople. To make sense of this connection, we conducted a meta-analysis using 89 studies to reveal the overall relationships between the most common psychopathologies and little-c creativity and uncover the source of variance in the relationships. The 89 studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 135 publications
2
34
0
1
Order By: Relevance
“…Previous studies have found enhanced divergent thinking and creativity in adults with ADHD compared to those without (White & Shah, 2006, 2016 though also see Barkley et al, 1996;Paek, Abdulla, & Cramond, 2016). White and Shah (2006) asked undergraduate students to complete the Remote Associates Test (Mednick, 1962), a measure of convergent thinking which asks participants to provide a specific word (e.g., house) that relates to each of three given (conceptually distant) words (e.g., outhouse, dog house, and white house), and an Alternate Uses task, a divergent thinking measure which asks participants to provide as many uses as possible for common objects (e.g., a newspaper or brick).…”
Section: Divergent Thinking Creativity and Adhdmentioning
confidence: 90%
“…Previous studies have found enhanced divergent thinking and creativity in adults with ADHD compared to those without (White & Shah, 2006, 2016 though also see Barkley et al, 1996;Paek, Abdulla, & Cramond, 2016). White and Shah (2006) asked undergraduate students to complete the Remote Associates Test (Mednick, 1962), a measure of convergent thinking which asks participants to provide a specific word (e.g., house) that relates to each of three given (conceptually distant) words (e.g., outhouse, dog house, and white house), and an Alternate Uses task, a divergent thinking measure which asks participants to provide as many uses as possible for common objects (e.g., a newspaper or brick).…”
Section: Divergent Thinking Creativity and Adhdmentioning
confidence: 90%
“…In fact, previous studies have often suggested a positive relationship between creativity and manifestations of mental illness, such as schizotypy, which is a tendency to have aberrant experiences that resemble milder versions of schizophrenia symptoms [39][40][41], especially positive schizotypy (odd perceptions and magical thinking) [42][43][44][45], bipolar disorder [41,46], and insomnia [47,48]. Although some articles reported that there were no significant relationships between creativity and mental illnesses such as attention deficit hyperactivity disorder, anxiety, social anxiety, negative affect, and depression [49,50], recently, Baas et al [46] integrated these findings that positive schizotypy and bipolar disorder were positively related to creativity, whereas negative schizotypy (physical and social anhedonia), depressed mood, and anxiety were negatively related to it.…”
Section: Introductionmentioning
confidence: 99%
“…Many creativity researchers have observed that the question, “Is creativity linked to mental illness?” is simply too broad (Silvia and Kaufman, 2010 ; Silvia and Kimbrel, 2010 ; Carson, 2019 ). Meta-analyses of studies of creativity and mental illness clarify that the answer varies depending upon research approach (Taylor, 2017 ); the types of psychopathology being investigated (Acar and Runco, 2012 ; Baas et al, 2016 ); the definition of creativity used, the measures used for both creativity and mental illness, the age at which creativity is measured, and the level of creativity of the participants (Paek et al, 2016 ). In general, effect sizes related to the link between creativity and mental illness are small; larger effect sizes tend to be found with specific subscales of measures; and stronger relationships tend to be found only in studies with adult eminent people and bipolar spectrum disorder, particularly in writers.…”
Section: Review Of the Literaturementioning
confidence: 99%